Peran Dinas Pemberdayaan Perempuan Dan Perlindungan Anak (Dp3a) Dalam Pencegahan Tindak Kekerasan Pada Anak Usia Dini di Karawang - Anisa Azzahra Swastha; Dadang Danugiri; Ika Rizqi Meilya (Peneliti.net, 2022)
The role of the Office of Women's Empowerment and Child Protection (DP3A) in preventing acts of violence against early childhood in Karawang. Faculty of Teacher Training and Education. Singaperbangsa University Karawang 2022. Aims to describe the role of DP3A in implementing the prevention program for violence against early childhood in Karawang in an effort to prevent the increase in cases of violence against early childhood. This research method uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. This research consisted of one party from the DP3A institution, one DP3A volunteer, and three victims of violence. The results showed that the program carried out by the DP3A district was running quite well which made changes to victims who dared to fight back when a crime occurred and parents became aware of the correct parenting pattern.